2002
DOI: 10.1046/j.1365-2648.2002.02208.x
|View full text |Cite
|
Sign up to set email alerts
|

The role of the district nurse in bereavement support

Abstract: Older age, higher qualifications and district of employment among district nurses were associated with greater interest in bereavement and more proactive care of bereaved people. The findings of this survey have important implications for the training, continued education and the extended role of the nurse in bereavement support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
47
1
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(52 citation statements)
references
References 22 publications
1
47
1
3
Order By: Relevance
“…as an important part of their roles 21,22 and a satisfying aspect of personal care provision, 23 although time pressures often result in it having low priority. 23,24 They recognise the major impact of loss 25 and see it as part of their duty to make contact with those who are recently bereaved, 22,26 although some question the appropriateness of doing so, fearing being an unwelcome reminder of the death 27 and medicalising grief.…”
Section: Gp and District Nurse Attitudes To Bereavement Carementioning
confidence: 99%
See 3 more Smart Citations
“…as an important part of their roles 21,22 and a satisfying aspect of personal care provision, 23 although time pressures often result in it having low priority. 23,24 They recognise the major impact of loss 25 and see it as part of their duty to make contact with those who are recently bereaved, 22,26 although some question the appropriateness of doing so, fearing being an unwelcome reminder of the death 27 and medicalising grief.…”
Section: Gp and District Nurse Attitudes To Bereavement Carementioning
confidence: 99%
“…A 2002 survey of district nurses found that 83% believed they had an important role in bereavement care and 82% thought they should make contact with patients who were bereaved. 21 Some district nurses, however, see this as, primarily, a GP responsibility 21 and view visiting people with whom they have no prior relationship as inappropriate practice. 29 Both groups recognise the need for interprofessional coordination within the primary care team.…”
Section: Gp and District Nurse Attitudes To Bereavement Carementioning
confidence: 99%
See 2 more Smart Citations
“…These units were chosen to get a rich variation concerning staff members' perceptions of providing bereavement follow-up in palliative care. In Sweden as well as in other countries palliative care and bereavement support is also considered to be part of primary care, not only a matter for specialized palliative care services [3,29]. Therefore, the study context was three advanced palliative home care teams (APHC) and three primary care services in Sweden.…”
Section: Study Populationmentioning
confidence: 99%